Design of a photomultiplier tube high-voltage power supply base for integration into three-dimensional additive manufacturing - Dodson, Miranda Leih (Kansas State University, 2021)
A photomultiplier tube high-voltage power supply was designed to be additively manufactured. It includes a Cockcroft-Walton voltage multiplier circuit for voltage multiplication. The low component count and small volumetric design is an alternative concept to typical Cockcroft-Walton ladders used to power photomultiplier tubes. When properly implemented, the Cockcroft-Walton ladder can be simplified in both component size and circuit implementation for hybrid three-dimensional printing. The new design simplifies embedding circuitry into three-dimensional shapes, while helping achieve minimal package footprint and reliability such that is it more compatible with three-dimensional printing of electronic circuitry. This work includes an overview of the Cockcroft-Walton ladder for use with photomultiplier tubes, basic nuclear pulse processing circuitry, an in-depth analysis of the Cockcroft-Walton configurations, and an initial design used as the basis of this research. Additionally, the Cockcroft-Walton control circuitry and ladder design were simplified and documented from component selection to finalized design. Finally, successful fabrication of a minimized Cockcroft-Walton voltage generation circuit on a standard printed circuit board was constructed. Basic benchmark testing was conducted with the circuit to analyze the efficiency in power consumption and performance using radiation spectroscopy with a Cesium Iodide scintillation crystal. A 16-stage Cockcroft-Walton ladder design was able to achieve power consumption reduction of 8%, 7.5mW to 6.9mW. Component count was reduced by 17%, 166 components to 137 components with simplification of circuit architecture. Energy resolution of the photomultiplier tube with Cesium Iodide scintillation crystal was able to achieve 7.8%, in comparison to the manufacturer engineered base at 7.5% under similar operating conditions.
Keywords: Cockcroft-Walton voltage multiplier